Strategies Used By Head Teachers And Ministry Of Education Officials To Strengthen Parent-Teacher Partnerships In Early Years: A Case Of Uasin Gishu County - Koech, Peter Kibet (International Journal of Innovative Research and Advanced Studies (IJIRAS), 2021)
The Kenyan Government in her partnership policy intends to promote the relationship between parents, teachers and the community in enhancing children’s education. This will be possible if: First, parentteacher partnerships were enhanced in Epstein’s six modes of involvement and partners’ roles were defined; second, varieties of techniques were employed; and finally, factors that relate to parent- teacher partnerships were appreciated and catered for. A parent-teacher partnership in Kenya was found to be low. Local researches in Kenya reveal minimum levels of parent-teacher partnership in primary and secondary schools. Studies show that the role of the community and parents was low and seemed to be restricted to the provision of finances and facilities. The purpose of this study was to explore parent- teacher partnerships and strategies used to promote these relationships in pre- schools. The study was done in Uasin Gishu District. Epstein’s Family, and Community Partnerships theory, Dunst, Johanson, Rounds, Trivet and Hamby’s Family Enabling Empowerment Model and Hoover-Dempsey and Sandler’s Model of Parental Involvement, guided it. This study used an Ex Post Facto design. The independent variable was strategies used. The dependent variable was parent-teacher partnerships. The target populations were parents and teachers of preschool, pre-school and primary school Head teachers and Ministry of Education Officials. The sample size consisted of 135 parents, 60 teachers, 10 Head teachers, 5 Ministry of Education Officials at the district level and 4 at the national level. Questionnaires and interview schedules were used for data collection. Data was prepared for statistical analysis using Statistical Package for Social Sciences. Means, percentages formed part of the descriptive statistics. ANOVA and t-test of independent samples were used and null hypotheses were tested at alpha value 0.05. Findings revealed that the level of parent-teacher partnerships was low. The most frequent strategies used by the Head teachers and Ministry of Education Officials were sending letters, organizing workshops on transition, holding parent’s teachers’ meetings, holding closing term meetings and providing information about children’s progress. The strategies used included sending information to the teachers through DICECE officers, organizing for sensitization meetings, organizing academic days, open visits by parents, and using class representatives. It was recommended that there is need to use appropriate strategies to promote partnerships for harmonious working relationship.